2013
DOI: 10.1089/pho.2012.3359
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Effects on Simulated Orthodontic Tension Side Periodontal Ligament Cells

Abstract: Objective: The purpose of this study was to analyze proliferation, inflammation, and osteogenic effects on periodontal ligament (PDL) cells after low-level laser therapy (LLLT) under simulated orthodontic tension conditions. Background data: Low-level lasers affect fibroblast proliferation and collagen synthesis and reduce inflammation. Few studies have focused on the LLLT changes in the PDL caused by moving teeth. Materials and methods: A human PDL cell line was cultured in a -100 kPa tension incubator. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
(18 reference statements)
2
30
0
Order By: Relevance
“…First, PBM increases the production of mitochondrial ATP, by upregulating the cytochrome c oxidase, 15,[23][24][25] and promotes cellular viability and the expression of osteocalcin in the tension areas of periodontal ligament (PDL). 13 This increased metabolic activity accelerates cellular turnover (osteoclast, osteoblast, and fibroblasts) 22,26 and the production of cytokines involved in the bone remodeling, mainly the IL-1b. 27 Second, PBM activates the receptor of nuclear factor kappa B (RANK) and the macrophage-colony stimulating factor along with its receptor (c-fms) that, respectively, seem to play a role in the expedition of dental movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, PBM increases the production of mitochondrial ATP, by upregulating the cytochrome c oxidase, 15,[23][24][25] and promotes cellular viability and the expression of osteocalcin in the tension areas of periodontal ligament (PDL). 13 This increased metabolic activity accelerates cellular turnover (osteoclast, osteoblast, and fibroblasts) 22,26 and the production of cytokines involved in the bone remodeling, mainly the IL-1b. 27 Second, PBM activates the receptor of nuclear factor kappa B (RANK) and the macrophage-colony stimulating factor along with its receptor (c-fms) that, respectively, seem to play a role in the expedition of dental movement.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Photobiostimulation is a noninvasive irradiation procedure that uses a laser light within the red to near-infrared range (wavelengths from 632 to 1064 nm) to provoke a biological reaction. In vitro studies reported that photobiostimulation accelerates cellular turnover by increasing the expression of osteocalcin, 13 stimulating angiogenesis, 14 and the availability of mitochondrial ATP. 15,16 In the orthodontic field, the assumption is that such increased metabolic activity could speed the rate of tooth movement, as confirmed by some clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…A major determinant of orthodontic tooth motion is the method of bone remodeling in the periodontal tissues, 29 affected by different local and systemic factors like nutrition, age, and medications 30,31 and internal factors such as cytokines, 32,33 interleukin-1β (IL-1β), and prostaglandins (especially PGE2). 34,35 LLLT has been considered to be effective in relieving pain, healing soft tissues, muscle relaxation, 36 immune system modulation, 37 fibroblast proliferation, 38,39 and nerve damage recovery. LLLT incites vascularization of the bone defect, fracture position, as well as osteoblasts, which can assist the recuperation of hard tissue.…”
Section: Discussionmentioning
confidence: 99%
“…14 It also improves the regeneration of periodontal tissue by increasing the proliferation and differentiation of osteogenic cells. 15 PBMT has been found to significantly increase cell viability, decrease cellular inflammatory marker expression, and increase osteoclast activity in PDL cells, 16 and to improve the quality of bone remodelling during OTM. 10 However, the literature reports conflicting results, since some authors say they found no differences in OTM acceleration between patient groups treated with PBMT and non-intervention groups.…”
Section: [ E P U B a H E A D O F P R I N T ]mentioning
confidence: 99%